Top Management Team Intrapersonal Functional Diversity and Adaptive Firm Performance: The Moderating Roles of the CEO–TMT Power Gap and Severity of Threat - Ma, Changlong; Ge, Yuhui; Wang, Jingwei (Frontiers in Psychology, 2021)
While usually argued to be improving firm performance, the effect of top management team (TMT) functional diversity on firm performance is mixed. Bridging the TMT diversity, team adaptation, and threat-rigidity literature, we present a contingency model in which the relationships between intrapersonal functional diversity (both at CEO and TMT level) and adaptive firm performance depend on the CEO-TMT power gap and the severity of threat. In order to test our hypotheses, 270 firms which have been severely damaged by the COVID-19 pandemic were selected from China’s A-share listed companies. Multiple regression analyses have shown that the moderation of CEO intrapersonal functional diversity’s effect on adaptive firm performance by CEO-TMT power gap is moderated by the severity of threat. However, no significant main or interaction effect of TMT intrapersonal functional diversity was found. The findings of this study have implications for the recovery or improvement of firm performance in threat situations.